Thermodynamic modelling of Al-Si-Cu alloys for semisolid processing - Salleh, Mohd Shukor; Omar, Mohd Zaidi; Syarif, Junaidi; Mohammed, Mohammed Naser (Penerbit Universiti Kebangsaan Malaysia, 2014)
Thixoforming is a new method in producing near net shape products which conducted in semisolid condition. This process can reduce macrosegregation, porosity and used low forming forces. Currently there are severals garde of aluminium alloys such as A319, A356 and A357 used in semi-solid metal processing. Therefore there is a demand to widen another grade of aluminium alloys specially tailored for semisolid metal processing. This study discusses the thermodynamic modelling to predict changes in the properties of aluminium alloy A319 expecially when the percentage content of alloying elements such as copper, manganese and iron is varies in order to fulfill the criteria of semisolid metal processing. The termodynamic modelling shows that the solidification temperature decreases from 130 to 113 celcius while the eutectic temperature increase from 510 to 515 celcius when the percentage of copper, mangan and ferum contents is increased. The liquid fraction sensitivity is reduced from 0.017 to 0.007 and teh working window temperature is reduced from 26 to 26 celcius. The results indicate the suitability of these modified alloys as a potential material for semisolid processing.